Purchasing Decisions for Pure Cow's Milk in Tlekung Junrejo Village Batu seen from Promotion, Price, and Product Quality - Muhammad Tody Arsyianto; Sudarmiatin Sudarmiatin; Ludi Wishnu Wardhana (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
This study set out to investigate and determine whether a product's quality, price, and promotion affect consumers' purchasing decisions. The study's demographic and sample consisted of eight respondents who solely drank pure cow's milk and lived in the Tlekung Junrejo Batu village. Questionnaires were used to collect data for this investigation. The data analysis methods used in this study include the Instrument Test, Normality Test, Hypothesis Test, Coefficient of Determination Test, Multiple Linear Regression Analyzer, and Classical Assumption Analyzer. SPPS is used to analyze this study process. Price, product quality, and advertising all have a positive and significant impact on the purchase of pure cow's milk in Tlekung Junrejo Village, Batu.